Farm-gate greenhouse gas emission intensity for medium to large New York dairy farms - Olivia F. Godber; Karl J. Czymmek; Michael E. van Amburgh; Quirine M. Ketterings (Journal of Dairy Science)
ABSTRACT: In 2022, New York had over 620,000 dairy cows producing more than 7 million Mg (15 billion pounds) of milk, ranking fifth in dairy producing states in the United States. The objectives of this work were to (1) estimate total farm-gate GHG emissions and GHG emission intensity (GHGei) of 36 medium to large (>300 mature cows) commercial New York dairies, (2) determine the contribution of main GHG (on-farm methane [CH4], nitrous oxide [N2O], and carbon dioxide [CO2], plus embedded emissions [CO2 equivalents; CO2eq]) and sources (enteric fermentation, feed production, manure management, grazing, fuel, and energy) to farm-gate GHGei, and (3) identify key performance indicators (KPI) driving farm-gate GHGei. Assessments were done for 2022 using the Cool Farm Tool. Farm size ranged from 345 to 6,350 head of predominantly Holstein cows, with animal densities between 1.76 and 4.85 animal units per hectare (0.71–1.96 animal units per acre), and heifer:cow ratios between 0.02 and 0.49. Herds produced an average fat and protein corrected milk (FPCM) yield of 12.7 Mg (29,000 lb) FPCM cow−1 per year using 64% homegrown feed. Total FPCM production was 873,000 Mg (1.92 billion lb), representing ∼12% of the total New York milk production in 2022. The GHGei ranged from 0.63 to 1.06 kg CO2eq kg FPCM−1 (mean GHGei = 0.86 kg CO2eq kg FPCM−1). Methane was the biggest contributor, accounting for 60% of total GHG emissions on average, with enteric CH4 as the largest contributor (45% of total farm emissions). Among farms, feed production emissions accounted for about 25%, with ∼7% from homegrown feed production. Manure management practices accounted for about 20% of emissions and explained the largest amount of variation in GHGei among farms. Potential KPI for GHGei included manure management system, heifer:cow ratio, herd feed consumption intensity, percentage of homegrown feed, and crop nutrient source (fertilizer vs. manure). Emission intensity reflected the high proportion of good quality homegrown feed, careful nutrient management, and use of manure treatment systems (covered liquid slurry storages, anaerobic digesters) on several dairies. The influence of replacement rate and heifer:cow ratio on animal density, herd feed consumption intensity, and subsequent GHGei requires more detailed analysis. The farms in this study represent a considerable proportion of New York's 2022 FPCM production. Greater participation by smaller farms is necessary to draw conclusions for New York's dairy industry as a whole.